Given $f \in C^3(\mathbb{R}).$ Suppose that $\lim\limits_{x\to+\infty}f(x)=a \in \mathbb{R}$ and $\lim\limits_{x\to+\infty}f'''(x)=0$. Prove that $\lim\limits_{x\to+\infty}f'(x)=\lim\limits_{x\to+\infty}f''(x)=0$.

My solution: Since $\lim\limits_{x\to+\infty}f(x)=a$, there exists $M>0$ that for all $x, x' \in \mathbb{R}$, if $x,x'>M$ then $f(x), f(x') \in \left(a-\varepsilon^2/2, a+\varepsilon^2/2\right)$. This yields $$\vert f(x)-f(x') \vert < \varepsilon^2.$$

Therefore $\frac{\vert f(x)-f(x') \vert}{\varepsilon} < \varepsilon$. So, for all $x>M$, $x'=x+\varepsilon$ we have $$0\le\frac{\vert f(x+\varepsilon)-f(x) \vert}{\varepsilon} < \varepsilon.$$ Let $\varepsilon \to 0$ we have $$0 \le f'(x) \le 0 \text{ or } f'(x)=0.$$

That means $\lim\limits_{x\to+\infty}f'(x)=0$.

Doing similarly as above we have $$\lim\limits_{x\to+\infty}f''(x)=0.$$

My question: $\lim\limits_{x\to+\infty}f'''(x)=0$ is really necessary or not (because I don't use it in my proof)?


Here's a proof that shows how the condition on the 3rd derivative could be utilized.

Take Taylor's remainder theorem to 3rd order and apply it to the intervals $(x,x+h)$, $(x,x+k)$, $h\neq k$. Now consider only the first interval since the second one can be done similarly.

There exists $\xi\in(x,x+h)$ such that $$f(x+h)=f(x)+f'(x)h+\frac{f''(x)}{2!}h^2+\frac{f'''(\xi)}{3!}h^3$$

Now since $\lim_{x\to\infty}f(x)=\lim_{x\to\infty}f(x+h)=a$, and $\lim_{x\to\infty}f'''(\xi(x,h))=0$ (why?) we conclude that $$\lim_{x\to\infty}\left(f(x+h)-f(x)-\frac{f'''(\xi)}{3!}h^3\right)=h\lim_{x\to\infty}\left(f'(x)+\frac{h}{2}f''(x)\right)=0 ~~~~~~~~~~(1)$$ Similarly we conclude $$\lim_{x\to\infty}\left(f'(x)+\frac{k}{2}f''(x)\right)=0~~~~~~~~~~~~~(2) $$

Taking the linear combinations $(2)-(1)$ and $h(2)-k(1)$ and exploiting the linearity of the limit operation when two limits exist, we obtain the desired result. The result is generalizable to a $C^n$ function whose $n$th derivative goes to zero for any $n$.

  • $\begingroup$ Related: math.stackexchange.com/a/3922194/42969. $\endgroup$ – Martin R Jan 18 at 19:11
  • $\begingroup$ +1 Thanks to the limit of $f^{(n)} $ being $0$, your proof is simple. The result holds even when $f^{(n)} $ is bounded but the proof gets a bit complicated. See math.stackexchange.com/a/731013/72031 $\endgroup$ – Paramanand Singh Jan 19 at 1:17
  • 1
    $\begingroup$ There is a typo in the third derivative in the Taylor polynomial, also the denominator is 6, not 3. $\endgroup$ – edm Jan 19 at 5:55

First, consider $$ f(x)=\frac{\sin(x^2)}{x}. $$ As $x\rightarrow\infty$, this approaches $0$. On the other hand, $$ f'(x)=\frac{2x^2\cos(x^2)-\sin(x^2)}{x^2}=2\cos(x^2)-\frac{\sin(x^2)}{x^2} $$ does not have a limit as $x\rightarrow\infty$. Therefore, the condition on $f'''$ is necessary for the result.

The problem with your setup is that you never specify when you're quantifying $\varepsilon$. You're actually quantifying it before computing $M$, so we'll write $M=M(\varepsilon)$. Next, you consider $$ \frac{|f(x+\varepsilon)-f(x)|}{(x+\varepsilon)-x}. $$ At this point, you let $\varepsilon$ go to $0$, but here's your problem, as $\varepsilon$ goes to $0$, $M(\varepsilon)$ may go to infinity, so you don't get a bound on the derivative when $\varepsilon$ is too small, so the squeeze theorem cannot be applied.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.